The impact of dimensions of concerning the distribution of daily Iraqi newspapers informing customer loyalty - جثير, سعدون حمود; عبد الحسين, سماء علي (Journal of Economics and Administrative Sciences, 2013)
AbstractThe study deal with two main variables:- the dimensions of distribution, and the customer loyalty . the researcher has chosen samples of Iraqi newspapers like (AL Sabah, AL Mada, AL Bayna aljdeida newspaper), because this product depends greatly on the consumption of customers so as to achieve the success. After studying the dimensions of these variables ( cost, flixibilty & deliver time ) which concerns the distribution, and for these dimensions ( marketing relationship, customer perception, customer experience, brand, & product quality) which relate to the customer loyalty . the problem has been identified in a number of remarks concerning the extent of awareness that the administration of the newspaper have about the importance of distribution and the delivery time of customer loyalty for achieving this success in continuation of the paper, the target of the administration must be on the techniques of the distribution and the reality of these newspapers. concluded that the time of delivery is the dimension of the most influential in building customer loyalty,  in spite of the awareness of management, there is reluctance to adjust the times of delivery of newspapers, in addition to the weakness in the mechanics of forming customer loyalty and maintain its Accordingly